Computika: A Mobile-based Interactive Learning Media for Computer Systems Subject in Vocational High Schools - Hidayat, Rahmat; Rian, Rahmad Al; Herlandy, Pratama Benny; Novalia, Melly (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2025)
Vocational high school students often face difficulties in understanding computer systems, creating the need for an innovative and interactive learning medium. This study aims to develop Computika, a mobile-based learning platform designed to enhance students’ comprehension of computer systems. The research employed a Research and Development (R&D) approach using the 4D development model (Define, Design, Develop, Disseminate). Validation was conducted by subject-matter experts, media experts, and tested on 21 students. The validation results indicated a very high level of feasibility: 100% from subject-matter experts, 94% from media experts, and positive responses from both students (94%) and teachers (91%). These findings confirm that Computika is highly feasible to be implemented as an innovative interactive learning solution that improves students’ understanding and learning motivation in computer systems courses.